(untitled) (Konferensiyalar | Conferences, 2024)
In recent years, Uzbekistan has vigorously developed the national language, issued various policies to improve the Uzbek language system, and promoted the Uzbek language overseas. As an important strategic partner of Uzbekistan, China attaches great importance to cultural exchanges with Uzbekistan. This article discusses the features of teaching Uzbek language as a foreign language to Chinese students, taking into account the specifics of the Chinese language and and the peculiarities of the Chinese mentality. The relevance of the study is due to the constantly growing interest in the Uzbek language in the Chinese society in connection with a noticeable increase in the number of all kinds of contacts between Uzbekistan and China. Our proposed work is based on the search for optimal ways to increase the effectiveness of teaching Uzbek as a foreign language to Chinese students. The purpose of the study is to theoretically substantiate and develop a phased system for teaching Uzbek as a foreign language to Chinese students. The main research methods were the analysis of the academic literature on the methodology of teaching Uzbek language as a foreign language, as well as diagnostic methods, including observation, description, conversation, questioning, testing, and methods of statistical data processing. The article contains comparative analyzes of linguistic systems in Uzbek and Chinese. On the example of practical material for teaching phrase logical units in Uzbek, containing zoonyms, the role of the native language in understanding the educational material at the early stage of training is shown.